Differential gene expression in the endometrium on gestation day 12 provides insight into sow prolificacy - Zhang, Hao (BioMed Central, 2013)
BACKGROUND: Erhualian pigs, one of Chinese Taihu pig breeds, are known to have the largest recorded litter size in the world. A lower prenatal death rate is the major contributing factor to the prolificacy of Taihu pigs. Cross-breeding experiments have demonstrated that Taihu sows exhibit a strong maternal effect and that their large litter sizes are mainly caused by maternal genes. The growth and development of porcine embryos on gestation day (GD) 12 are dependent on histotroph secreted by endometrium. Embryonic loss of Taihu pigs on GD12 is lower than that of Western pigs. Here, endometrial samples were collected from pregnant Erhualian sows (parity 3) and Landrace × Large White (LL) sows (parity 3) on GD12. Digital gene expression profiling (DGE) was used to measure the gene expression in the endometrium of the two breeds. RESULTS: A total of 13,612 genes were differentially expressed between the two breeds (P < 0.001, FDR < 0.001). Gene Ontology (GO) analysis showed that the differential genes involved in reproduction and growth. Pathway analysis revealed that the differentially expressed genes significantly enriched in 24 KEGG pathways. Quantitative real-time RT-PCR confirmed the differential expression of eight genes. Analyses of the differentially expressed genes suggested possible reasons for the difference in embryonic survival ratio between the two breeds. Specifically, these findings point to a higher ratio of PGE(2):PGF(2α) in the endometrium of Erhualian pigs, which facilitates the establishment and maintenance of pregnancy. We also suggest that the differences in the uterine environment lead to higher uterine capacity in Erhualian pigs. CONCLUSIONS: The DGE expression profiles of Erhualian and LL endometrium demonstrated differential expression of genes. Our results will increase understanding of the molecular mechanisms of the low rate of embryonic loss in Chinese Taihu pigs, facilitate the identification of major genes that affect litter size, and be valuable for porcine transcriptomic studies.